Penentuan Dimensi Pipa Pada Lapangan Panasbumi Gedongsongo - Pramudiohadi, Eko Widi (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
To meet the demand for electricity in the Ungaran area in particular, it is necessary to build geothermal power in the Gedongsongo area, but there are no production facilities, both below and on the surface, so the authors plan production facilities on the surface, regarding the selection of optimum pipe diameters. The goal is to build a power plant with a capacity of 110 MWe based on the optimum diameter, which provides the smallest possible loss of pressure and temperature and the maximum possible mass flow, for this the authors use the pressure loss profiles from Begg and Brill and temperature loss using the 1st law of thermodynamics, With two-dimensional Newton Rapson manipulation, it can be seen that the drop in pressure and temperature at the exit point simultaneously on a pipe segment. In this field, there are 4 clusters, including: cluster 1 (4 wells), cluster 2 (5 wells), cluster 4 (2 wells), each 2 wells served by 1 separator, starting from the pressure of each wellhead 15 Barg, dryness 0.25 and rate 105.5 kg/s, insulation thickness 8 cm, polyurethane type, pipe length from wellhead to separator 150 m, resulting in pipe diameter from 18-24 in, minimum thickness from 30.82-39.62 mm, pressure drop 0.55 Barg, temperature 1.67 oC, from separator to turbine input, pipe 50-1200 m long, yield diameter from 16-48 in, minimum thickness 25.01-61.50 mm, pressure drop 1.61 Barg, temperature 3.11 oC, with a generated power of 154 MWe